VASOPRESSOR THERAPY OF HEPATORENAL SYNDROME AGAINST THE BACKGROUND OF ALCOHOLIC LIVER CIRRHOSIS - Slyvka, N.O.; Lukashiv, T.O.; Rusnak, I.T.; Sydorchuk, A.S.; М. В. О. Аль Салама; Rovinskyi, O.O.; Akentiev, S.O. (World of Medicine and Biology, 2021)
Hepatorenal syndrome is one of the most common causes of death in liver cirrhosis, and its treatment methods are insufficiently studied, therefore, the aim of this study was to compare the effectiveness of different schemes of vasopressor therapy. A total of 109 patients with alcoholic liver cirrhosis were divided into two groups: group 1 (n=57) – received terlipressin+albumin, group 2 (n=52) – midodrine+octreotide+albumin. According to the study results, there was a significant difference in the cumulative 3–month survival in groups 1 and 2 (56.1 % vs. 28.8 %, p˂0.05). In the multivariate analysis, only the complete response to treatment (risk ratio – 23.92; p˂0.002) and the initial severity scores (risk ratio – 1.18; p˂0.02) were predictors of 3–month survival. Terlipressin showed greater therapeutic efficacy, as it reduced mortality risk by 3.65 times (from 0.558±0.034 to 0.153±0.026) (p